Severe blunt external laryngotracheal trauma: surgical outcome - Raja Lope Ahmad, Raja Ahmad Al'konee (2009)
Blunt external laryngotracheal trauma is rarely encountered in clinical practice. Most of the time, the first attending doctor overlooks this injury. Surgical management for this trauma is complicated, since there is no common management approach for this potentially life-threatening injury. It is important that this injury to be identified early as delay in surgical intervention may result in poor airway and speech outcome. The aim of surgical reconstruction is to minimize the debilitating morbidity from the trauma by restoring as much as possible the main laryngeal functions of airway and speech. We reviewed four cases of severe blunt external laryngotracheal trauma and assessed the outcome of the surgical interventions. One patient had associated cervical trauma and none of them had concomitant esophageal injury. All patients made a good recovery in term of airway function, but most of them except one developed reduced speech function. The technique of surgical reconstruction is highlighted in this report. The surgical treatment depends on the site of injury either in the larynx or tracheal. In both situations stenting are needed to help normal healing and re-epithelization to take place. In conclusion, prompt recognition and airway controlled are required in laryngotracheal trauma. Surgical emphysema is an important hallmark that should alert the attending physician to the possibility of severely laryngotracheal trauma. Immediate surgical intervention with appropriate surgery in this problem may result in favorable outcome.